Irradiation testing of ASICs for the HL-LHC ATLAS ITk Strip Detector. (23rd February 2023) - Dandoy, J.R.; Dressnandt, N.C.; Gosart, T.C.; Gutierrez Zagazeta, L.F.; Keener, P.T.; Krizka, K.; Kroll, J.; Lipeles, E.; Lu, S.; Mayers, G.; McGovern, R.P.; Newcomer, F.M.; et al.
Abstract: For the high-luminosity upgrade to the LHC, the ATLAS Inner Detector will be replaced by an all-silicon tracker (ITk) consisting of two systems: pixels and strips. HCC and AMAC are ITk Strip ASICs vital for performing the system readout, monitoring, and control. To ensure these ASICs will successfully operate in the high-radiation environment of the HL-LHC, they need to be tested for radiation tolerance, and tests have been performed using both heavy ions and protons. The ASIC designs were shown to protect against single event effects due to radiation.